Compliance with Sharia Principles in Property Business in Indonesia: An Analysis of Murabahah Contracts in Sharia Bank Mortgages - Mahmud, La Ode; Pattih, Iskandar; Bakti, Bakti; Unga, Wa Ode Harliyanti; Elmabgoul, Abdallah (Islamic Research, 2024)
Abstract This study aims to evaluate the implementation of the Murabahah contract in Home Ownership Loans (KPR) by Islamic banks in Indonesia against Sharia principles. A qualitative analysis revealed that while the Murabahah contract is widely used, several practices do not fully comply with Sharia principles. These non-compliant practices include schemes resembling riba, selling products not yet owned, and inconsistencies in project management by Islamic banks. The findings indicate that adherence to Sharia principles significantly impacts customer trust and satisfaction, thereby affecting customer loyalty to Islamic banks. The study highlights the necessity for increased supervision and stricter application of Sharia principles in property transactions. The Sharia Supervisory Board (DPS) and transparency in reporting are crucial for maintaining integrity and trust in Islamic financial institutions. This research significantly contributes by identifying areas requiring improvement to ensure full compliance with Sharia principles in the property business, providing a solid foundation for developing Sharia-compliant property business practices.